Testing the model of dispositional employability in a sample of Croatian job seekers - Maslić Seršić, Darja (Array, 2014)
According to the dispositional model of employability, employability is defined as a multidimensional person-centered construct which subsumes five dimensions (openness to changes at work, work and career resilience, work and career proactivity, career motivation and work identity) which promote proactive adaptability in a work context. The aim of the present study was to empirically test the model in a Croatian sample of unemployed persons of different biographic characteristics (N = 567 ; N = 155 in a follow-up study). Specifically, a hypothesized model of dispositional employability (DE) was tested with a CFA. Moreover, we tested relationships with perceived employability, job-search intensity and re-employment success. The results of our study supported the hypothesized structure of the DE model which defines it as a second-order latent factor subsuming five dimensions. In addition, it's predictive validity was confirmed with DE predicting perceived employability and job-search intensity. However, re-employment success was not predicted by DE in a follow-up study.